2000
DOI: 10.1016/s0090-3019(99)00179-2
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 concentration increases in the cerebrospinal fluid in cerebral vasospasm caused by subarachnoid hemorrhage

Abstract: We confirmed that the concentration of ET-1 in CSF increased before the onset of cerebral vasospasm caused by subarachnoid hemorrhage. The ET-1 concentration in the CSF could be a useful marker to detect cerebral vasospasm after subarachnoid hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 19 publications
1
26
0
2
Order By: Relevance
“…Our observation that subjects with evidence of severe vasospasms (higher CBFV) exhibit higher ET-1 concentrations in CSF is in accordance with some [5][6][7][8][9]35 but not all 9 earlier studies that reported possible associations between ET-1 levels and cerebrovascular complications. It must be noted that ET-1 may also act in a paracrine fashion 36 ; therefore, a strong correlation between ET-1 concentration and vasospasm is not mandatory to establish the pathogenetic importance of ET-1 in SAH.…”
Section: Faßbender Et Al Et-1 In Subarachnoid Hemorrhage 2973supporting
confidence: 91%
“…Our observation that subjects with evidence of severe vasospasms (higher CBFV) exhibit higher ET-1 concentrations in CSF is in accordance with some [5][6][7][8][9]35 but not all 9 earlier studies that reported possible associations between ET-1 levels and cerebrovascular complications. It must be noted that ET-1 may also act in a paracrine fashion 36 ; therefore, a strong correlation between ET-1 concentration and vasospasm is not mandatory to establish the pathogenetic importance of ET-1 in SAH.…”
Section: Faßbender Et Al Et-1 In Subarachnoid Hemorrhage 2973supporting
confidence: 91%
“…ET-1 concentrations in the CSF of patients after SAH were significantly elevated compared with control groups, consisting mainly of healthy volunteers and patients with another neurologic nonhemorrhagic disease, such as hydrocephalus or degenerative spinal disease. [2][3][4][5][6][7][8] In patients who did not develop CV, ET-1 concentrations decreased gradually with time, 6,8 whereas CV patients exhibited a significant increase between days 4 and 7 posthemorrhage and postsurgery. 3,8,9 This increase coincided with the occurrence of symptomatic CV.…”
Section: Endothelin-1mentioning
confidence: 99%
“…Several studies showed a secondary rise in ET-1 coinciding with the development of cerebral vasospasm, whereas there was no rise in ET-1 in those without vasospasm [14]. Endothelins are also presumed to have a significant effect on secondary brain injury after TBI, with many putative roles ascribed to the ET A and ET B receptors in animal models [15][16][17].…”
Section: Introductionmentioning
confidence: 99%